Organizational identification and voice: exploring the moderating effect of socio-moral climate - Gonçalves, J.; Tavares, S. M.; Silva, S.A.; Ribeiro, A. (III Symposium on Ethics and Social Responsibility Research, 2015)
In spite of the existence of some studies about voice behavior, only a few relate these behaviors with the socio–moral climate (SMC). This research intends to fill this gap by analyzing the moderating effect of the SMC in the relationship between organizational identification and promotive voice behavior. Thus, we applied surveys composed by scales thoroughly validated to 315 employees of diversified organizations. The results revealed that the workers with higher levels of organizational identification have more promotive voice behaviors only when they have a positive perception of SMC. These findings suggest that along with organizational identification, the improvement of organizational SMC is essential to enhance employee’s voice behavior.